FAX-RIC enables robust profiling of dynamic RNP complex formation in multicellular organisms in vivo. Issue 5 (17th December 2020) - Na, Yongwoo; Kim, Hyunjoon; Choi, Yeon; Shin, Sanghee; Jung, Jae Hun; Kwon, S Chul; Kim, V Narry; Kim, Jong-Seo
Abstract: RNA–protein interaction is central to post-transcriptional gene regulation. Identification of RNA-binding proteins relies mainly on UV-induced crosslinking (UVX) followed by the enrichment of RNA–protein conjugates and LC-MS/MS analysis. However, UVX has limited applicability in tissues of multicellular organisms due to its low penetration depth. Here, we introduce formaldehyde crosslinking (FAX) as an alternative chemical crosslinking for RNA interactome capture (RIC). Mild FAX captures RNA–protein interaction with high specificity and efficiency in cell culture. Unlike UVX-RIC, FAX-RIC robustly detects proteins that bind to structured RNAs or uracil-poor RNAs (e.g. AGO1, STAU1, UPF1, NCBP2, EIF4E, YTHDF proteins and PABP), broadening the coverage. Applied to Xenopus laevis oocytes and embryos, FAX-RIC provided comprehensive and unbiased RNA interactome, revealing dynamic remodeling of RNA–protein complexes. Notably, translation machinery changes during oocyte-to-embryo transition, for instance, from canonical eIF4E to noncanonical eIF4E3. Furthermore, using Mus musculus liver, we demonstrate that FAX-RIC is applicable to mammalian tissue samples. Taken together, we report that FAX can extend the RNA interactome profiling into multicellular organisms. Graphical Abstract: